Makna Zuhud Dalam Kehidupan Prespektif Tafsir Al-Qurâ€™an - Abdul Muqit (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
In this day and age, many people misunderstand zuhud. Many think that zuhud is leaving wealth, rejecting enjoyment of the world, and forbid the lawful. The interpretation that has been given by the Sufis in the early period on the meaning of zuhud in Islam all relating to a pessimistic view of world life. Therefore, this world should know and the splendour and enjoyment of worldly life should be rejected. Even though Islam requires itâ€™s people to prosper the earth, work, and rule the world, but at the same time not be deceived by the world. In this modern era, culture, economy, social, and religion are not spared the influence of modernization as a from of advanced civilization which actually has an â€œeffect sideâ€ which is so complex, society often displays the characteristics that less praiseworthy, especially in the face of this sparkling material. Impact in fact it is a society that is becoming more consumerist and individualism. In this case, it is necessary to practice to be a simple life, waraâ€™, and patience. As well as trying to get rid of boasting, knowing that this world is only temporary.